Implementasi Model Pembelajaran Berbasis Masalah dalam Pendidikan IPA: Trend dan Peluang Penelitian Menggunakan Systematic Literature Network Analysis - Nurhayati; Andi Suhandi; Muslim; Ida Kaniawati (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this study is to describe research trend data related to the implementation of PBL in science education. Article metadata was collected from the SCOPUS database, and 131 relevant articles were selected in 2013-2022. Data were analyzed using the Systematic Literature Network Analysis (SLNA) method with the VOSViewer application. Variables of bibliometric analysis, such as the number of articles and citations each year, the journals and authors with the most publications, countries, and networks of authors' cooperation, were determined based on metadata and analyzed descriptively. This research shows that the number of PBL research articles in science education during the 2013-2022 period fluctuated and tended to increase. The top keywords with the highest link strength are science, teacher, and technology. Recent research focuses on modules/e-modules, scientific literacy, natural science, and physics as important keywords. Future research related to the use of PBL learning has the potential to be developed in physics material and focuses on developing 21st-century skills such as creative thinking, critical thinking, communication, and collaboration. In addition, further research can focus on developing the knowledge and skills of prospective teachers in implementing PBL models that are integrated with 21st-century skills.